Behavioural health risks during early adolescence among perinatally HIV-infected South African adolescents and same-age, HIV-uninfected peers. Issue 1 (2nd January 2019) - Brittain, Kirsty; Myer, Landon; Phillips, Nicole; Cluver, Lucie D.; Zar, Heather J.; Stein, Dan J.; Hoare, Jacqueline
ABSTRACT: Behavioural health risks, including substance use, early sexual debut, bullying and suicidality, are common during adolescence, but may be complicated among perinatally HIV-infected adolescents. However, there are few data exploring these behaviours in sub-Saharan Africa. We compared behavioural health risks (any self-report of substance use, sexual activity, bullying others or suicidality, or a positive urine toxicology screen) among perinatally-infected adolescents ages 9–14 years to that of an HIV-uninfected comparator group; and explored the effect of behavioural health risks on adolescent and caregiver report of adolescent suboptimal adherence (missed antiretroviral therapy dose(s) on ≥1 day during the preceding 30 days) and elevated HIV viral load (≥50 and ≥1000 copies/mL in sensitivity analyses) in multivariable logistic regression models. Among 506 HIV-infected and 110 HIV-uninfected adolescents (median age overall: 12 years), 15% and 25% reported any behavioural health risk (p = 0.018), respectively. Tobacco and other drug use was uncommon, while alcohol use was reported by 8% of HIV-infected versus 12% of HIV-uninfected adolescents (p = 0.185). One HIV-infected (0.2%) and 3 HIV-uninfected adolescents (3%) reported any sexual activity (p = 0.019). Among HIV-infected adolescents, report of any behavioural health risk was more common among male adolescents [adjusted odds ratio (aOR): 1.78; 95% confidence interval (CI): 1.08–2.95] and was associated with adolescent report of suboptimal adherence (aOR: 1.66; 95% CI: 0.99–2.78) but not with caregiver report of suboptimal adherence or with elevated viral load. In this group of perinatally-infected youth entering early adolescence, the prevalence of behavioural health risks was lower than that among same-age, HIV-uninfected peers. Longitudinal data are needed to explore the reasons underlying these differences, for example the possibility of more protective caregiving and supportive family environments, or of emotional and physical immaturity, as well as the emergence of risk behaviours over time in this population.